Cost-effectiveness analysis of metronomic capecitabine as adjuvant chemotherapy in locoregionally advanced nasopharyngeal carcinoma - She, Longjiang; Tian, Kun; Han, Jiaqi; Zuo, Weihan; Wang, Zhu; Zhang, Ning (Frontiers in Oncology, 2022)
Background: Adding metronomic capecitabine to concurrent chemoradiotherapy (CCRT) brings failure-free survival (FFS) benefits to patients with locoregionally advanced nasopharyngeal carcinoma (NPC). This study aims to assess the cost-effectiveness of metronomic capecitabine in locoregionally advanced NPC. Methods: We created a Markov model to calculate the expense and health outcomes of metronomic capecitabine in comparison to that observed in locoregionally advanced NPC. Related costs, life-years (LYs), quality adjusted life years (QALYs), and incremental cost-effective ratios (ICERs) were measured at a willingness-to-pay (WTP) threshold of 33585 per QALY. A combination of different sensitivity analyses was used to test for model robustness. Additionally, a subgroup analysis was also performed. Results: In contrast to what is observed in the locoregionally advanced NPC, adding metronomic adjuvant capecitabine yielded an additional 1.11 QALYs with an incremental cost of 10741.59 which obtained an ICER of 9669.99 per QALY. The result of one-way sensitive analysis indicated that the utility of FFS and progression disease (PD), and the cost of follow-up were the most significant factors. The probability of metronomic capecitabine being cost-effective was 97.1% at a WTP of 33585 per QALY. Conclusion: Metronomic capecitabine as adjuvant chemotherapy is a cost-effective strategy for locoregionally advanced NPC patients.